2009
DOI: 10.1016/j.otsr.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty in patients with greater than 20 degrees flexion contracture

Abstract: Level 4 retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…It has been shown that preoperative knee stiffnessdefined by a preoperative ROM of 50°or less [5] significantly impairs the overall clinical outcome [6][7][8]. Additionally, higher complication rates have been reported due to difficulties in knee exposure, soft tissue balancing and iatrogenic injury to the extensor mechanism or patellar tendon [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that preoperative knee stiffnessdefined by a preoperative ROM of 50°or less [5] significantly impairs the overall clinical outcome [6][7][8]. Additionally, higher complication rates have been reported due to difficulties in knee exposure, soft tissue balancing and iatrogenic injury to the extensor mechanism or patellar tendon [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate soft tissue balancing in the form of ligament and capsular release at the time of arthroplasty is essential to the success of TKA procedures, which not only achieves an obvious correction of the flexion contracture but also effectively improves the range of motion and the functional recovery of the knee joint after TKA 9,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The TKA surgical procedure included a standard anteromedial approach, the use of an intramedullary femoral and extramedullarytibial alignment rod, measured bone resection, and differential ligament balance in flexion and extension 9 . Measured resection implies that the amount of bone resected from the intact compartment of the joint equals the thickness of the implant, while restoring correct alignment by resecting the bone perpendicular to the mechanical axis.…”
Section: Table Imentioning
confidence: 99%
See 1 more Smart Citation
“…Although function and pain is markedly improved with arthroplasty, full correction of flexion contractures has proven to be much more difficult. Massin et al 10 recently reported the outcome of 107 TKA's performed to correct both flexion contracture of greater than 20 and knee stiffness. As a result of the arthroplasty, extension increased by an average of 20 with a residual flexion contracture of 7 in the flexion contracture only group.…”
Section: Discussionmentioning
confidence: 99%